2021
DOI: 10.1017/ice.2021.193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) mRNA vaccination in healthcare workers with high-risk coronavirus disease 2019 (COVID-19) exposure

Abstract: Appropriate precautions for fully vaccinated healthcare providers following high risk household SARS CoV-2 exposure remains unknown. Herein, we report initial results from our employee health protocol for such situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Most SARS-CoV-2 infections in vaccinated personnel occurred after higher-risk exposures to family members. As noted previously, Selby et al 6 reported that such exposures may present a substantial risk to vaccinated individuals. Our findings provide support for recommendations that vaccinated individuals continue to take measures to avoid SARS-CoV-2 exposure.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Most SARS-CoV-2 infections in vaccinated personnel occurred after higher-risk exposures to family members. As noted previously, Selby et al 6 reported that such exposures may present a substantial risk to vaccinated individuals. Our findings provide support for recommendations that vaccinated individuals continue to take measures to avoid SARS-CoV-2 exposure.…”
mentioning
confidence: 67%
“…[1][2][3][4][5] In a recent report, 5 (12%) of 43 fully vaccinated personnel acquired mildly symptomatic or asymptomatic SARS-CoV-2 infection after higher-risk household exposures. 6 Ongoing surveillance studies are needed to determine whethe such postvaccination "breakthrough" infections are caused by variants of concern with reduced in vitro susceptibility to neutralization by vaccine-induced antibodies. 7 Surveillance studies can also provide comparative data on COVID-19 in unvaccinated personnel.…”
mentioning
confidence: 99%
“…Smaller studies on fully vaccinated healthcare workers who subsequently developed SARS-CoV-2 infections demonstrated rates of breakthrough infection between 0.05% and 11.6%. 8 , 9 , 10 , 11…”
Section: Introductionmentioning
confidence: 99%
“…Smaller studies on fully vaccinated healthcare workers who subsequently developed SARS-CoV-2 infections demonstrated rates of breakthrough infection between 0.05% -11.6%. [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%